Calibration of T 2 oximetry MRI for subjects with sickle cell disease - Bush, Adam; Vu, Chau; Choi, Soyoung; Borzage, Matthew; Miao, Xin; Li, Wenbo; Qin, Qin; Nederveen, Aart J.; Coates, Thomas D.; Wood, John C. (Magnetic resonance in medicine, 2021)
Cerebral T oximetry is a non-invasive imaging method to measure blood T and cerebral venous oxygenation. Measured T values are converted to oximetry estimates using carefully validated and potentially disease-specific calibrations. In sickle cell disease, red blood cells have abnormal cell shape and membrane properties that alter T oximetry calibration relationships in clinically meaningful ways. Previous in vitro works by two independent groups established potentially competing calibration models. This study analyzed pooled datasets from these two studies to establish a unified and more robust sickle-specific calibration to serve as a reference standard in the field. Even though the combined calibration did not demonstrate statistical superiority compared to previous models, the calibration was unbiased compared to blood-gas co-oximetry and yielded limits of agreement of (-10.1%, 11.6%) in non-transfused subjects with sickle cell disease. In transfused patients, this study proposed a simple correction method based on individual hemoglobin S percentage that demonstrated reduced bias in saturation measurement compared to previous uncorrected sickle calibrations. The combined calibration is based on a larger range of hematocrit, providing greater confidence in the hematocrit-dependent model parameters, and yielded unbiased estimates to blood-gas co-oximetry measurements from both sites. Additionally, this work also demonstrated the need to correct for transfusion in T oximetry measurements for hyper-transfused sickle cell disease patients and proposes a correction method based on patient-specific hemoglobin S concentration.